HADIS IDEOLOGI PERSPEKTIF HIZBUT TAHRIR - Ahmad Zainal Mustofa Zainal (Program Studi Ilmu Hadis Fakultas Ushuluddin Adab dan Dakwah IAIN Langsa, 2019)
Hizbut Tahrir is an Islamic ideology based on the Qur'an, hadith and ijma of the companions. This party was established in 1953 in Palestinian al-Quds with Taqiyuddin an-Nabhani as first leader. They want to establish an Islamic state that is based on the Qur'an and hadith regarding the rules of the syariat law. There are three foundations for their movement to uphold the khilāfah, namely: philosophical foundation, normative foundation and historical foundation. They argue that khilāfah is not an idea or an idea, but a product of history that has existed in the world. This study focused on the history, ideology and literature hadith as quoted by Hizbut Tahrir to legitimize their arguments for establishing an Islamic state. There are many weaknesses in their understanding of the hadith of the hadith, so impressive that Hizbut Tahrir is an inconsistent and often subjective party in interpreting a hadith.